Situating the discourse of recycled nutrient fertilizers in circular economy principles for sustainable agriculture - Cordeiro, Cheryl Marie; Sindhøj, Erik (Frontiers in Sustainability, 2024)
This mini review explores the integration of recycled nutrient fertilizers (RNFs) into practices for sustainable agriculture within the circular economy framework. Regional nutrient imbalances challenge the efficiency of implementing nutrient recycling and concerns about contaminants such as potentially toxic elements, microplastics, and antibiotic resistance genes hinder the adoption of RNFs. This review examines the technological, environmental, economic, and policy dimensions of nutrient recycling, highlighting how these practices align with circular economy principles to promote resource efficiency, waste reduction and reduced environmental impact. The review underscores the importance of economic feasibility, supportive policies, and public perception in facilitating RNF adoption. Technological innovations like struvite precipitation and biochar production show promise but face challenges such as high costs and contamination risks. Effective policy frameworks and stakeholder engagement are crucial for broader acceptance. This interdisciplinary review draws insights from environmental science, economics, and agricultural engineering, contributing to a comprehensive understanding of how RNFs can enhance sustainable agricultural practices. The findings suggest that with continued technological innovation, effective contamination management, supportive policies, and incentives to enhance market demand, and educating stakeholders about the benefits and safety of RNFs to improve public perception and adoption, can significantly contribute to a more sustainable and resilient agricultural system.